2015
DOI: 10.1002/ccd.25899
|View full text |Cite
|
Sign up to set email alerts
|

Valve‐in‐valve‐in‐valve: Treating endocarditis of a transcatheter heart valve

Abstract: Transcatheter heart valve endocarditis is a rare, but life threatening complication. We describe the case of a patient who was successfully treated by transcatheter aortic valve-in-valve-in-valve replacement with a favorable 1-year outcome, despite severe early complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Furthermore, our literature search identified only 4 cases of early-stage of IE successfully treated by TAVR. 4 , 5 , 6 , 7 We found that all of them shared several features with our case, including: 1) cardiogenic shock caused by severe valvular dysfunction as the main surgical indication; 2) identified causative microorganism that was susceptible to antimicrobial therapy; and 3) prohibitively high surgical risk. Likewise, all those patients recovered and remained asymptomatic, with no evidence of infection >6 months after the index event.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, our literature search identified only 4 cases of early-stage of IE successfully treated by TAVR. 4 , 5 , 6 , 7 We found that all of them shared several features with our case, including: 1) cardiogenic shock caused by severe valvular dysfunction as the main surgical indication; 2) identified causative microorganism that was susceptible to antimicrobial therapy; and 3) prohibitively high surgical risk. Likewise, all those patients recovered and remained asymptomatic, with no evidence of infection >6 months after the index event.…”
Section: Discussionsupporting
confidence: 68%
“…Уровень кольца каркасного биопротеза при рентгеноскопии должен использоваться в качестве контрольного уровня для фиксации ТК [23][24][25]. Если при имплантации при рентгеноскопии получается форма песочных часов, это может нарушать работу створок имплантированного протеза и этого следует избегать [23].…”
Section: Discussionunclassified
“…In 2013, Albu et al described the first case of a healed IE in a severe aortic homograft stenosis successfully treated with a self-expandable TAVI [7]. In 2015, Nguyen et al described the first case of valve-in-valve-in-valve procedure to treat a healed IE in a patient treated with TAVI inside a surgical bioprosthetic valve by a second time successful TAVI [9].…”
Section: Discussionmentioning
confidence: 99%